Digital Threads, Interwoven Scenes - Emmi Holm (Suomen Antropologi)
A lectio præcursoria is a short presentation read out loud by a doctoral candidate at the start of a public thesis examination in Finland. It introduces the key points or central argument of the thesis in a way that should make the ensuing discussion between the examinee and the examiner apprehensible to the audience, many of whom may be unfamiliar with the candidate’s research or even anthropological research in general.